Pretreatment method for utilizing landfill coal ash

A pretreatment method for landfilled coal ash using screening, float-sink, and magnetic sorting processes enhances recycling efficiency and produces high-purity by-products for industrial use, addressing the challenges of coal ash disposal and pollution.

JP7617109B2Active Publication Date: 2025-01-17NATIONAL INSTITUTE OF ENVIRONMENTAL RESEARCH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022538165
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-02-18
Filing Date
2022-03-07
Publication Date
2025-01-17
Estimated Expiration
2042-03-07

AI Technical Summary

Technical Problem

The challenge of effectively recycling landfilled coal ash from coal-fired power plants is significant due to its mixture of fly ash and bottom ash, environmental contamination risks, and the high cost of constructing new landfill ponds, leading to substantial disposal in landfills which can pollute soil and water.

Method used

A pretreatment method involving screening, float-sink, flotation, and magnetic sorting processes to separate landfilled coal ash into Fe oxide-containing and Si/Al-containing fine materials, unburned carbon, and amorphous compounds, enhancing recycling efficiency.

Benefits of technology

The method increases the recycling rate of landfilled coal ash by producing high-purity by-products suitable for various industrial applications, reducing environmental pollution risks and lowering disposal costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007617109000010
    Figure 0007617109000010
  • Figure 0007617109000011
    Figure 0007617109000011
  • Figure 0007617109000012
    Figure 0007617109000012
Patent Text Reader

Abstract

The present invention relates to a pretreatment method for utilizing landfill coal ash (coal ash buried in a landfill pond near a coal-fired power plant), and more particularly to a pretreatment method for landfill coal ash that can utilize coal ash at a high level through simple separation processes such as screening, float-sink, floatation, grinding, and magnetic separation.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pretreatment method for utilizing landfill coal ash, and more particularly, to a pretreatment method for landfill coal ash that can utilize landfill coal ash at a high level through simple separation processes such as screening, float-sink, floatation, grinding, and magnetic separation. [Background technology]

[0002] Coal ash (CA) is inorganic waste that remains after combustion in the blast furnaces of coal-fired power plants (CPPs). Coal ash is broadly divided into fly ash (collected by electrostatic precipitators) and bottom ash (collected at the bottom of the boiler). The particle size is widely distributed from less than 0.1 μm to more than 5 cm in diameter, and the main components are silicon dioxide (SiO2), aluminum oxide (Al2O3), iron oxide (Fe2O3), calcium oxide (CaO), and magnesium oxide (MgO) (Lee, S. et al., Renew. Sust. Energy Rev. 50, 186-193, 2015; Liang, W. et al., J. Energy Inst. 93, 642-648, 2020). Coal ash has been used in industrial sites as a recyclable material and can play an essential role as a new alternative resource. For this reason, many countries are making policy efforts to turn coal ash into a new alternative resource. In South Korea, in order to increase the recycling rate of coal ash, it was listed as a recyclable by-product in the "Act on Resource Conservation and Recycling Promotion" announced by the Ministry of Environment (Ministry of Environment, 2020). In addition, a list of coal ash recycling items that can be approved by the government without government permission was provided in the "Recycling Guidelines for Businesses Discharging Steel Slag and Coal Ash (Notification No. 2016-217, Ministry of Environment) (Ministry of Environment, 2016)." The inventory includes 16 items: concrete admixtures such as ready-mix concrete, cement raw material, lightweight aggregate, raw material for secondary cement products, aggregate for embankments, aggregate for covering soil, aggregate for roads, raw material for wood adhesives, substitute for raw material for cement clinker production, aggregate for drainage layers, ceramic materials, rubber and plastic fillers, raw material for paints, abrasives and insulation materials, raw material for steel and steel, and raw material for soil fertilizer. In the United States, different laws and regulations apply to coal ash in each state. The Pennsylvania Department of Environmental Protection has developed "Beneficial Uses of Coal Ash" in accordance with the Solid Waste Management Act (Department of Environmental Protection, 2021).In Europe, the use of coal ash is regulated by Directive 2008 / 98 / EC "to improve the management of wastes containing coal ash and to promote reuse and recycling" (European Union Law, 2008). Japan is currently focusing on ensuring the quality and environmental safety of recycled products to increase the efficiency of recycled coal ash. The responsibility for environmental safety applies to producers, intermediate contractors, and end users respectively (Sato, K. et al., 2015. Japanese Goetechnical Society Special Publication 3, 65-70). China has set a series of commercial coal quality standards, including private coal standards, while strengthening coal management. This has led the central and local governments in China to implement preferential policies such as financing or tax exemptions for projects that use coal ash (Bai, X. et al., 2017, Int. Geol. Rev. 60, 535-547). Some experts have also put forward some measures, such as: First, an improved government-led support system (e.g., road toll exemptions, financial lending support, stabilizing the recycling market, and expanding channels for demand for recycled products) is needed to promote domestic coal ash recycling (UNDP, 2017, Sustainable Development Goals (Policy Brief Series): Examples of Korea's Successful Policies in Waste Management & Lessons Learned That Could Apply in Other Countries (Accessed 24 June 2021)). Second, producers' responsibility for coal ash recycling must be strengthened (UNEP, 2010). Third, the range of recyclable products must be expanded (Ministry of Environment, 2016). Fourth, a private-public consultative body must be formed, including the government, coal-fired power plant officials, and recyclers, to continually discuss additional measures to increase the domestic coal ash recycling rate.

[0003] However, despite these efforts, some coal ash types depend on landfill pond treatment type. For example, the amount of coal ash produced at coal-fired power plants in Korea in 2017 was up to 9.4 million tons (MT). Of this, the amount recycled was the highest at 8.0 MT (85.1%). However, landfill disposal was 1.4 MT (14.9%), followed by incineration (less than 0.1 MT, <1%) (Um, N. et Al., 2018. Study on the Performance Improvement of Domestic Management System for Effective Control of Transboundary Movements of Waste. National Institute of Environmental Research, Incheon (South Korea)). In addition, in the case of recycling, the use of coal ash as an alternative raw material for cement and auxiliary fuel for cement was the highest at 7.1 MT (88.8%), followed by filler and covering material (0.4 MT, 5%). It can be seen that coal ash recycling is intensively dependent on the cement industry in bricks (0.2MT, 2.5%) and other fields (0.3MT, 3.8%). For example, studies on the use of coal ash in the cement industry have been actively carried out, such as its utilization as cement resources and concrete aggregates (Mangi,SA et al.,2019.Resources 8(2),99;Navdeep,S.et al.,2019.Resour.Conserv.Recycl.144,240-251;Qin,Q.et al.,2020,Bioresour.Technol.318,124055), reuse of shortcrete and building materials (Anghelescu,L.et al.,2019.Constr.Build.Mater.227,116616;Kim,H.et al.,2009.Mater.Sci.Forum 620-622,251-254). In addition, the physical properties were investigated for applications such as recycling cement materials (Rifal, A. et al., 2009, Advances in Environmental Geotechnics. Springer, pp. 715-720).Such biased research and utilization means that although coal ash is included in the recycling item catalog recommended by the government, its low quality makes it difficult to use as a raw material in other recycling fields. In addition, recyclers give priority to direct recycling methods that omit pretreatment processes in order to save on additional costs such as transportation, processing, and facility installation. Ultimately, the physical and chemical composition (characteristics) of coal ash may not meet the quality standards required for recycled products. This concern is not limited to Korea. In Europe, only 13 MT of a total of 30 MT of coal ash was recycled in 2016, of which >70% was used as an alternative raw material for cement (raw material, mixed cement, and added to concrete) (European Coal Combustion Products Association, 2021). In the United States, only 41 MT of a total of 110 MT of coal ash was recycled as a cement raw material for the production of concrete, concrete products, and grout in 2018 (EPA, 2021). In China, the overall utilization of coal ash has been gradually increasing in recent years, but the recycling rate remains below 70% due to a rapid increase in the amount of coal ash generated, restrictions on the transportation radius, and the deterioration of the quality of coal ash as a raw material (He et al., 2012).

[0004] The coal ash generated at 11 nuclear power plants in Korea (Hadong, Taean, Yeosu, Yeongdong, Yeongheung, Samcheonpo, Donghae, Honam, Danjin, Sachon, Boryeong) is disposed of in landfill ponds near the coasts of each coal-fired power plant. There are ~265 coal-fired power plant sites in the United States, and most of these sites have coal ash landfill ponds (Environmental Integrity Project, 2019). There are 38 coal-fired power plants in Japan. Since the Great East Japan Earthquake in 2011, there has been a major shift from nuclear power generation to thermal power generation, and as a result, coal-fired power generation now plays an important role as a stable source of electricity (Sato, K. et al., 2015, Japanese Goetechnical Society Special Publication 3, 65-70). Generally, the coal ash disposed of in landfill ponds consists of a mixture of fly ash and bottom ash. Fly ash may have different properties from bottom ash, since the particles are spherical or sharp, the fine particle size is less than 0.1 μm, and the particle size distribution is uniform. However, when fly ash is landfilled, it is mixed with the bottom material, and both are landfilled without separate treatment. As can be seen from the landfill volume, it is expected that at least a certain amount of coal ash will continue to be landfilled in the landfill pond area every year in the future. In fact, most of the landfill ponds are filled up, so the construction of new landfill pond areas is essential. However, construction is difficult due to the high cost of landfill construction and local residents who are concerned about the possibility of contamination of the surrounding environment. For example, a report showing land contaminated by coal ash throughout the United States questions the quality of the groundwater in the area. 91% of all sites had unsafe levels, which was shown to be affected by on-site reclamation ponds (Environmental Integrity Project, 2019; Vengosh, A. et al., 2019, Sci. Total Environ. 686, 1090-1103). In Africa, a large coal mine is being developed in Mozambique, which is planned to become a hub for large coal-fired power plants that will supply electricity to neighboring South Africa.However, such activities increase the possibility of contamination by coal ash (Marove, CA et al., 2020, J. Afr. Earth Sci. 168, 103861). In China, coal ash treatment plants at 14 Chinese power plants were investigated. The investigation found more than 20 different toxic substances, including heavy metals and chemicals that are harmful to human health and the environment. It was found that in some areas, cows and sheep suffered from diarrhea, reduced birth rates and increased mortality after eating grass contaminated by coal ash. It was also found that neither the surface water nor well water around many coal-fired power plants met official standards (Si, M., 2010. Coal Ash Cloud Looms Large Over China. Inside Climate News (Accessed 24 June 2021)). In India, Khan and Umar conducted experiments around coal ash landfill ponds at coal-fired power plants to evaluate the potential impact of coal ash on soil and groundwater quality. This study showed that coal ash landfill ponds release toxic elements into water and soil, resulting in soil and groundwater pollution, leading to health and environmental problems (Khan, I. Umar, R., 2019. India. Groundw. Sustain. Dev. 8, 346-357), therefore, treating the huge amount of coal ash (herein referred to as "landfill coal ash") that is generally buried in landfill ponds is one of the major problems in the world. The only alternative to reduce the amount of landfill coal ash is to improve the quality of landfill coal ash as a raw material in resource circulation by using all possible pretreatment technologies. However, in order to utilize landfill coal ash, three things must be confirmed. First, landfill coal ash is a mixture of fly ash and bottom ash, so its characteristics must be investigated. Second, the characteristics of each coal-fired power plant may affect landfill coal ash. Thirdly, since the reclaimed ponds around coal-fired power plants are located in coastal areas, the reclaimed coal ash can be affected by seawater, which is a salt solution containing a large amount of chloride anions (19.344 g / kg Cl) (Ito, K. et al., 2009, Comprehensive Handbook of Iodine, pp. 83-91).

[0005] Therefore, the inventors have made extensive efforts to solve the above problems and increase the recycling rate of landfill coal ash, which is generated in large quantities at coal-fired power plants. As a result, they have confirmed that the recycling rate of landfill coal ash can be increased to a considerable level by performing simple separation processes, such as screening, float-sink, floatation, grinding, and magnetic separation, under optimal conditions, and have completed the present invention. Summary of the Invention

[0006] An object of the present invention is to provide a method for pretreating landfill coal ash, which can increase the recycling rate as a preliminary step before utilizing the landfill coal ash.

[0007] In order to achieve the above object, the present invention provides a method for pre-treating coal ash, comprising: (a) screening landfill coal ash using a sieve to classify the landfill coal ash into coarse particles, medium particles, and fine particles; (b) subjecting the fine particles obtained in step (a) to floatation; (c) subjecting the medium particles obtained in step (a) to gravity separation (float-sink); and (d) mixing the residue obtained in step (c) with the residue obtained in step (b), followed by magnetic separation to obtain fine materials containing Fe oxides and fine materials containing Si and Al.

[0008] The present invention also provides a method for obtaining a by-product having increased purity of unburned carbon (UC) and amorphous components (AC) from landfill coal ash (CPA), the method including: (a1) screening and recovering landfill coal ash; (a2) screening, flotation and recovering the landfill coal ash; (a3) ​​screening, gravity separation, pulverization, flotation and recovery of the landfill coal ash; (a4) screening, gravity separation, magnetic separation and recovery of the landfill coal ash; (a5) mixing a by-product obtained by screening, gravity separation, primary magnetic separation and pulverization of the landfill coal ash with the residue obtained in step (a2), and then subjecting the mixture to secondary magnetic separation and recovery; or (a6) magnetic separation and recovery of the residue obtained in step (a5).

[0009] The present invention also provides a method for obtaining a by-product having an increased recovery rate of Fe oxide from landfill coal ash (CPA), the method including: (b1) screening and recovering landfill coal ash; (b2) screening, flotation and recovering the landfill coal ash; (b3) screening, gravity separation and recovering the landfill coal ash; and (b4) mixing a by-product obtained by screening, gravity separation and pulverizing the landfill coal ash with the residue obtained in the step (b2), followed by magnetic separation and recovery; or (b5) magnetic separation and recovery of the residue obtained in the step (b4).

[0010] The present invention also provides a method for obtaining only Fe oxides from landfill coal ash (CPA), the method including: (c1) a step of crushing, magnetically separating, and recovering landfill coal ash; or (c2) a step of crushing, first magnetically separating, second magnetically separating, and recovering landfill coal ash.

[0011] The present invention also provides a method for obtaining only Fe oxides from landfill coal ash (CPA) to reduce the energy cost of the crushing process, further comprising a magnetic separation step before the crushing steps (c1) and (c2).

[0012] The present invention also provides a method for obtaining only unburned carbon and Fe oxides from landfill coal ash (CPA), the method including: (d1) a step of pulverizing, flotation, and recovering the landfill coal ash; (d2) a step of pulverizing, flotation, magnetic separation, and recovering the landfill coal ash; or (d3) a step of pulverizing, flotation, primary magnetic separation, secondary magnetic separation, and recovering the landfill coal ash.

[0013] The present invention also provides a method for obtaining an increased strength by-product from landfill coal ash (CPA), the method comprising: (e1) screening and recovering the landfill coal ash; (e2) screening, flotation and recovering the landfill coal ash; or (e3) screening, gravity separating and recovering the landfill coal ash. [Brief description of the drawings]

[0014] [Figure 1] 1 is a map showing the locations of 10 coal-fired power plants (CPPs) and 7 reclamation ponds (APs) in South Korea according to the present invention. [Diagram 2] FIG. 2 is a diagram showing an XRD pattern of landfill coal ash (CPA) according to an embodiment of the present invention. [Diagram 3] 1 is a scanning electron microscope photograph showing images of coal landfill ash (CPA) according to one embodiment of the present invention: amorphous components (AC) (Al species and glass phase) (a), coarse particles containing spherical Fe oxides of Fe2O3 and Fe3O4 (b), unburned carbon (UC) (c), mullite (d), and quartz (e). [Figure 4] Figure 1 shows the weight, distribution of unburned carbon (UC) and amorphous compounds (ACs) (including Al species and glass phase) of coal landfill ash (CPA) separated using gravity separation process with various specific gravities (SGs) according to one embodiment of the present invention (a), and XRD pattern (b). Experimental conditions: solid / liquid 200 (g / L), reaction temperature 20°C, reaction time 4 hours, stirring speed 100 rpm, CCl4 and CH2Br2 reagents for SGs. [Diagram 5]Figure 1 shows the effect of pH on the adsorption kinetics of unburned carbon (UC) (a), BET (Brunauer-Emmett-Teller) adsorption isotherm (b), and (CO-C) / C vs. Co / CO-C)Usec (c) according to an embodiment of the present invention. Experimental conditions: 13 (g / L) solid / liquid (a), and 6.5, 13, 19.5, 26, 39, and 52 (g / L) solid / liquid (b); 20°C reaction temperature; 60 s reaction time (a), and 10 s reaction time (b); 10 L / min flow rate of air gas; and 0.5 g / L kerosene and 0.08 g / L MIBC. [Figure 6] In one embodiment of the present invention, (a) shows the change in particle size distribution of landfill coal ash (CPA) with grinding time, (b) shows scanning electron microscope images of landfill coal ash (CPA), (c) shows particles of untreated landfill coal ash (CPA) (left side), and (b) shows particles of landfill coal ash (CPA) ground for 20 minutes. [Figure 7] 1 is a graph showing the change in the recovery rate (YFe) and purity (PFe) of Fe oxides of iron material separated by various magnetic forces of 0.1, 0.5, 1, and 2 T. [Figure 8] Schematic flow diagram of the pretreatment process for the separation of final by-products from landfill coal ash (CPA), including unburned carbon (UC), Fe oxides, amorphous compounds (AC) containing Al species (Al2O3·xH2O) and glass phase, and inorganic materials mainly composed of Si and Al. [Figure 9] There are various designs of pretreatment process depending on the condition of final by-product. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. Generally, the nomenclature used herein is well known and commonly employed in the art.

[0016] In the present invention, a pretreatment method was considered as a preliminary step before utilizing landfill coal ash (CPA). This method does not mean that landfill coal ash (CPA) can be directly recycled after removing or stabilizing certain hazardous substances, but corresponds to an intermediate process including a simple separation method to increase the recycling efficiency of the final recycling process. In order to design a pretreatment method required for effective utilization of landfill coal ash (CPA), various investigations were carried out using landfill coal ash (CPA) samples collected from an amphibious pond (AP) located near a coal-fired power plant (CPP) in Boryeong, Korea. First, the characteristics of the collected samples were investigated based on the chemical composition, particle size distribution, XRD (X-ray diffraction) analysis, and SEM (Scanning Electron Microscopy) images. Next, we designed a pretreatment method with simple separation processes of screening, float-sink, floatation, grinding, and magnetic separation according to the characteristics of landfill coal ash (CPA), and conducted experiments to obtain the optimal conditions for each separation process. Finally, we confirmed the applicability of the pretreatment method to landfill coal ash (CPA) in Korea and around the world.

[0017] The abbreviations used throughout the specification of the present invention are as follows: Coal ash is abbreviated as CA, coal-fired power plants is abbreviated as CPP, ash ponds is abbreviated as AP, and coal pond ash is abbreviated as CPA.

[0018] This invention proposes a method to increase the utilization of coal ash (CPA) in landfill ponds (APs) where coal ash (CA) generated from coal-fired power plants (CPPs) is buried, because of concerns about the possibility of environmental pollution around these ponds. Therefore, CA buried in APs is considered as CPA. In addition, CPA characteristics (particle size and weight distribution, chemical composition, unburned carbon (UC) content, particle image, and mineralogical analysis) were investigated. Next, experiments were conducted on the main separation processes: gravity separation experiments using four different specific gravities (SG) of less than 1.8 SG, 1.8-2.2 SG, 2.2-2.5 SG, and over 2.5 SG; flotation in a column-type glass reactor under pH 2, 7, and 12 conditions; grinding in a batch ball mill for 5, 10, 20, and 40 minutes; and wet magnetic separation using four magnetic forces (0.1, 0.5, 1, and 2 T). Based on these results, a pretreatment method was proposed, and the final by-products could be classified into UC, amorphous compounds (ACs) including Al species (Al2O3·xH2O) and glass phase, inorganic substances including Si and Al, and iron substances. Six further pretreatment methods were proposed by various combinations of each separation process. It was also confirmed that this method can be applied not only to the entire CPA in Korea but also to CPAs around the world.

[0019] Therefore, the present invention relates to a method for pre-treating coal ash, the method including: (a) screening landfill coal ash using a sieve to classify it into coarse particles, medium particles, and fine particles; (b) subjecting the fine particles obtained in step (a) to floatation; (c) subjecting the medium particles obtained in step (a) to gravity separation (float-sink); and (d) mixing the residue obtained in step (c) with the residue obtained in step (b), followed by magnetic separation to obtain Fe oxide-containing fine materials and Si and Al-containing fine materials. The present invention will be described in detail below.

[0020] In the present invention, in step (a), the particles can be classified into coarse particles having a diameter exceeding 2.36 mm, medium particles having a diameter of 0.15 to 2.36 mm, and fine particles having a diameter less than 0.15 mm, using standard sieves with meshes of 0.15 mm and 2.36 mm diameters.

[0021] In the present invention, the step (b) is carried out by adding a pH adjusting agent to stabilize the mixture to the most suitable pH, and then the desired by-products are collected by floating them on the water surface, followed by dehydration and drying. The step (b) may be carried out at pH 7.

[0022] There are several factors to consider when performing the flotation process. First, whether or not the material is wetted by water. The important medium in flotation is water, and flotation is about using the difference between materials that are familiar (well wetted) with water and those that are not (well wetted). If the surface of the solid to be obtained is not wetted by water, the solid will stick to air bubbles generated in the water (materials that are wetted by water will not stick to air bubbles), and will rise to the surface of the water together with the air bubbles due to the upward force of the air bubbles. If these air bubbles are removed and collected, a high-quality by-product will be obtained. Second, the size of the particles. It is important to make all the particles as uniform as possible during the flotation process. This is because it is difficult to match the specific gravity if the size is not uniform. In addition, the weight must be such that it can stick to the air bubbles and rise, and the size must be such that the target mineral and gangue minerals can be reliably separated.

[0023] In the present invention, in step (c), gravity separation can be performed using a solution having a specific gravity of 2.2.

[0024] In the present invention, after performing step (c), the method may further include a step of subjecting the obtained residue to magnetic separation at a magnetic field strength of 1.0 T, and grinding the separated Fe oxide-containing material.

[0025] In the present invention, in step (d), a mixture of the residue obtained in step (c) and the residue obtained in step (b) is subjected to a 0.1T wet magnetic separator to separate high-purity Fe oxide-containing fine materials, and then a 1.0T wet magnetic separator is used to separate low-purity Fe oxide-containing fine materials.

[0026] Additionally, the pretreatment method according to the present invention may be modified by various combinations of the separation steps to selectively obtain the desired end by-products.

[0027] Therefore, another aspect of the present invention relates to a method for obtaining a by-product having increased purity of unburned carbon (UC) and amorphous components (ACs) from landfill coal ash (CPA), the method including: (a1) screening and recovering landfill coal ash; (a2) screening, flotation and recovering landfill coal ash; (a3) ​​screening, gravity separation, pulverization, flotation and recovery of landfill coal ash; (a4) screening, gravity separation, magnetic separation and recovery of landfill coal ash; (a5) mixing a by-product obtained by screening, gravity separation, primary magnetic separation and pulverization of landfill coal ash with a residue obtained in step (a2), and then subjecting the mixture to secondary magnetic separation and recovery; or (a6) magnetic separation and recovery of the residue obtained in step (a5), the method being as shown in FIG. 9(a).

[0028] Yet another aspect of the present invention relates to a method for obtaining a by-product having an increased recovery rate of Fe oxide from landfill coal ash (CPA), the method including: (b1) screening and recovering landfill coal ash; (b2) screening, flotation and recovering the landfill coal ash; (b3) screening, gravity separation and recovering the landfill coal ash; and (b4) mixing a by-product obtained by screening, gravity separation and pulverizing the landfill coal ash with the residue obtained in the step (b2), followed by magnetic separation and recovery; or (b5) magnetic separation and recovery of the residue obtained in the step (b4), the method being as shown in FIG. 9(b).

[0029] Yet another aspect of the present invention relates to a method for obtaining only Fe oxides from landfill coal ash (CPA), comprising: (c1) a step of crushing, magnetically separating, and recovering landfill coal ash; or (c2) a step of crushing, primary magnetically separating, secondary magnetically separating, and recovering landfill coal ash, the method being as shown in (c-1) of FIG. 9.

[0030] Here, in order to reduce the energy cost of the process, magnetic separation can be further carried out before the grinding in (c1) and (c2), as shown in FIG. 9 (c-2).

[0031] Yet another aspect of the present invention relates to a method for obtaining only unburned carbon and Fe oxides from landfill coal ash (CPA), the method including: (d1) crushing, flotation, and recovering the landfill coal ash; (d2) crushing, flotation, magnetic separation, and recovering the landfill coal ash; or (d3) crushing, flotation, primary magnetic separation, secondary magnetic separation, and recovering the landfill coal ash, the method being as shown in (d) of FIG. 9.

[0032] Yet another aspect of the present invention relates to a method for obtaining an increased strength by-product from landfill coal ash (CPA), comprising the steps of: (e1) screening and recovering the landfill coal ash; (e2) screening, flotation and recovering the landfill coal ash; or (e3) screening, gravity separating and recovering the landfill coal ash, the method being as shown in FIG. 9(e).

[0033] Below, preferred examples are presented to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present invention. Naturally, such changes and modifications also fall within the scope of the appended claims. EXAMPLES

[0034] A CPP located in Boryeong area, which mainly uses bituminous coal, was selected, and CPA samples for all experiments were collected from APs located around the selected CPPs. A total of nine CPA samples were collected from three sites in APs, as shown in Figure 1. Each sample weighed 200 kg. Samples with various moisture contents were dried at 100°C for 24 hours. They were then passed through five standard sieves (Test Sieves, 200 x 50 mm) with meshes of diameters of 0.15, 0.3, 0.6, 1.18, and 2.36 mm to obtain samples with the required particle sizes, such as less than 1.15, 0.15-0.3, 0.3-0.6, 0.6-1.18, 1.18-2.36, and over 2.36 mm.

[0035] Example 1: Confirmation of the physical properties of CPA The chemical composition of CPA and the contents of Si, Al, Fe, Ca, Mg, K, Na, Ti, and Mn were measured using an X-ray fluorescence spectrometer (XRF 3726AI, Rigaku). The content of unburned carbon (UC) was determined using the Korean standard LOI method (ES 06303.1) (Ministry of Environment, 2011). 20 g of the dehydrated sample was taken and heated in an electric furnace at 815°C for 3 hours. After drying in a desiccator, the UC content (w / w.%) was evaluated from the weight difference before and after LOI. The initial amount of Cl was obtained after dissolving in an acid solution. The concentration of Cl dissolved after acid digestion was measured using ion chromatography (ICS-3000, Dionex). To confirm the mineralogical stage, CPA samples that were untreated or treated with a specific separation method were measured by XRD (PW3040 / 00, Philips). In addition, the surface of the target particles was analyzed using a scanning electron microscope (JEOL).

[0036] To confirm the characteristics of CPA collected from the AP near Boryeong CPP, we investigated the particle size distribution, chemical composition, particle image, and mineralogical analysis. Table 1 shows the weight distribution by particle size. The particle size of 1.18 mm or more showed a low weight distribution of 2.5%, and the value increased as the particle size decreased, except for 2.36 mm or more. In particular, the content of 0.3 mm or less accounted for 78.2% of the total content. In the chemical composition of CPA by particle size, Si, Al, Fe, and Ca were the main elements, accounting for more than 75% of the total composition. Among them, silica-based and alumina-based substances were uniformly distributed throughout the entire particle size. The content of Fe increased as the particle size became smaller. For example, the content of particle sizes of 2.36 mm or more was <0.1%. However, the content of particle sizes of 0.15-0.3 and less than 0.15 mm was 15.6% and 18.8%, respectively.

[0037] Table 1 shows the UC content of each particle size, which is evenly distributed across the entire particle size range, while the UC content of the particle sizes of 2.36 mm and 1.18-2.36 mm or more was the highest at 28.4% and the lowest at 9.3%, respectively. For Cl, the contents (mg / kg) of CPA samples with particle sizes of 2.36 mm or more, 1.18-2.36, 0.6-1.18, 0.3-0.6, 0.15-0.3, and 0.15 mm or less were 42, 74, 112, 184, 273, and 392, respectively. The AP around Boryeong Power Plant is located near the coast, and CPA can be influenced by seawater because seawater is a saline solution and contains a lot of chloride anions (19.344g / kg Cl) (Ito,K.et al.,2009.Chapter9-Indine and Iodine Species in Seawater:Speciation,Distribution,and Dynamics.Comprehensive Handbook of Iodine,pp.83-91). Most of the Cl in CA was removed by the washing process with water, and it was determined to be soluble chloride. From the XRD pattern of CPA in Figure 2, mullite (3Al2O3·2SiO2), quartz (SiO2), calcite (CaCO3), magnetite (Fe3O4), and corundum (Al2O3) can be observed. These peaks provide evidence that CPA is composed mainly of Si, Al, Fe, and Ca, as shown in Table 1. It can be seen that the background peak changes to Ω form as the x-axis angle moves from 15θ to 35θ. This provides evidence for the presence of amorphous compounds (AC) with UC (Bartonova, L., 2015. Fuel Process. Technol. 134, 136-158; Tai, FC et al., 2009, J. Raman Spectrosc. 41, 933-937) and Al species (Al2O3·xH2O) and glass phase (Kim, B. et al., 2019. The Korean Ceramic Society 56, 365-373; Yan, K. et al., 2018, J. Non. Solids 483, 37-42). Figure 3 shows SEM images of CPA particles. Among them, Figure 3(a) shows AC on the particle surface of CPA.Also, Figure 3(b) shows the shape of CPA containing spherical Fe oxides. When bituminous coal is burned in CPP, the Fe element of coal is dissolved and oxidized, and then aggregated as small spherical particles (Sharonova, O. et al., 2015, Energy Fuels 29, 5404-5414; Sokol, E. et al., 2002. Fuel 81, 867-876). In particular, the particle size of most of the Fe oxides is less than 0.15 mm. Since Fe oxides have relatively high strength compared to other CPA materials, even after the CPA is naturally crushed or crushed by external impact during landfilling in AP or transportation to AP, the Fe oxides maintain their spherical shape and exist independently with particle sizes less than 0.15 mm. Next, Figures 3(c), 3(d), and 3(e) show the UC, mullite, and quartz components, respectively.

[0038] Table 1 shows the chemical composition and weight distribution of landfill coal ash (CPA) for each particle size fraction (the experiment was repeated three times and each data was determined, and the standard deviation of each data was estimated). [Table 1]

[0039] Example 2: Pretreatment step 2-1: Gravity sorting (Float-sink) All gravity sorting experiments were carried out by adding 120 g of each sample to 600 mL of solution with four different specific gravities (SG) in a 1 L batch glass reactor maintained at 20 °C with a hot plate stirrer. The mixture was stirred for 0.5 h with a stirring speed of 100 rpm using a temperature-controlled magnetic stirrer. The four different SGs were prepared by mixing carbon tetrachloride (CCl4) and dibromomethane (CH2Br2) in the desired ratio. In the experimental procedure, the first experiment was carried out with 1.8 SG solution. Then, the sample precipitated by 1.8 SG was taken and added to 2.2 SG solution for the second experiment. Finally, the third experiment was carried out with 2.5 SG solution using the sample precipitated by 2.2 SG. After the experiments, four final by-products were obtained that belong to four SG ranges: less than 1.8 SG, 1.8-2.2 SG, 2.2-2.5 SG, and more than 2.5 SG.

[0040] 2-2: Flotation All flotation experiments were carried out in a column-type glass reactor with a diameter of 6 cm and a volume of 1.5 L by adding the desired amount of sample to 1 L of solution. The bottom of the reactor was connected with a hose, and air was injected inside at a flow rate of 10 L / min. A glass filter was placed between the hose and the bottom, which had the effect of reducing the size of the air bubbles and dispersing them widely. In addition, kerosene (0.5 g / L) and MIBC (0.08 g / L) were used to maintain the air bubbles for a long period of time and to enhance the adsorption effect of UC with the air bubbles. The pH value was adjusted to 2, 7, and 12 using hydrochloric acid (HCl) and sodium hydroxide (NaOH), respectively, to confirm the pH effect on flotation. In the experimental procedure, experiments were carried out for 60 seconds using 26 g of sample at each pH condition to confirm the pH effect on UC adsorption kinetics. In addition, to confirm the BET (Brunauer-Emmett-Teller) adsorption isotherm, experiments were carried out for 10 seconds using six samples of 6.5, 13, 19.5, 26, 39 and 52 g.

[0041] 2-3: Grinding All grinding experiments were carried out using a batch mill (SH-BALL700B, Weus) with a diameter of 200 mm, an inner diameter of 160 mm, and a length of 180 m. The balls, which were ~1.6 mm in diameter, were packed into the mill so that the ratio of the ball volume to the inner space volume of the mill was 0.4. The sample was then packed into the mill so that the sample volume per free space volume inside the mill filled with boro was 1.2. The mill was then rotated at the critical speed. JPEG0007617109000002.jpg7170 The mixture was rotated for each grinding time (5, 10, 20 and 40 minutes) and ground.

[0042] 2-4: Magnetic separation All magnetic separation experiments were carried out using a wet magnetic separator (Laboratory High Gradient Magnetic Separator: L-HGMS, DAE BO MAGNETIC CO., LTD.). An electromagnet that generates a magnetic field by electric current was placed outside the center of the separator, and the samples were allowed to fall freely through the separator. The magnetic force required for the experiment was maintained at 0.1, 0.5, 1, and 2 T by adjusting the electric current.

[0043] Example 3: An effective separation process for CPA Considering the above-mentioned characteristics of CPA, seven main points for selecting an effective separation process are presented in the design of the pretreatment process, the details of which are as follows:

[0044] Point 1: CPA consists of four main by-product groups: UC, Fe oxides, AC including Al species (Al2O3·xH20) and glass phase, and inorganic materials containing Si and Al.

[0045] Point 2: Particles over 2.36 mm have a high UC content and almost no Fe content. Therefore, by screening, particles over 2.36 mm can be separated to obtain coarse particles with a high UC content.

[0046] Point 3: In CPA, UC and AC, which have relatively smaller SG values ​​than other materials, can be separated using SG characteristics. Therefore, a gravity separation process with a separation principle using SG differences can be considered (Wills, BA et al., 2016. Wills' Mineral Processing Technoloty, pp. 245-264). However, small particles below 0.15 mm are not separated efficiently.

[0047] Point 4: The UC content of particles smaller than 0.15mm is 10.5%, which is not high compared to other CPA particle sizes. However, 41.2% of the total UC content is present in particles smaller than 0.15mm, which is the highest in the UC weight distribution. Therefore, for CPA particles smaller than 0.15mm, UC separation can be the main process. Here, flotation can be considered for the separation process (Eisele, TC et al., 2010. Miner. Process. Extr. Metal. Rev. 23, 1-10; Zhang, R. et al., 2019. Waste Manag. 98, 29-36; Zhou, F. et al., 2017. Fuel 190, 182-188).

[0048] Point 5: In general, Fe oxides can be easily separated using magnetic separation. In addition, if spherical Fe oxides with particle sizes of 0.15 mm or less are liberated from CPA as shown in Figure 3, the separation effect can be improved. Therefore, a crushing process (0.15 mm or less) for liberation may be considered before the magnetic separation process.

[0049] Point 6: According to points 1, 2, 3, 4 and 5, the particle size classification of CPA should be considered to improve the separation efficiency of the four major by-product groups. Therefore, three particle size ranges can be classified: over 2.36 mm, 0.15-2.36 mm and less than 0.15 mm.

[0050] Point 7: Coastal seawater affects the Cl content of CPA during cooling in the AP. However, most of the content is soluble chloride, which can be easily removed by simply operating the wet separation process.

[0051] Detailed experimental factors for gravity separation, flotation, crushing, and magnetic separation were investigated according to the points mentioned above. For gravity separation, the GS value for effective separation of UC and AC was confirmed. For flotation, the pH effect on UC separation was confirmed from the BET model with multi-layer adsorption between air bubbles and UC particles. In addition, crushing and magnetic separation experiments provided the liberation effect of Fe oxide from CPA after crushing and the effect of different magnetic forces on the recovery rate and purity of Fe oxide from CPA, respectively. The detailed contents are explained below.

[0052] 3-1: Gravity selection Gravity sorting was performed in four SG ranges, namely, less than 1.8SG, 1.18-2.2SG, 2.2-2.5SG, and over 2.5SG, to confirm the distribution percentage of weight, UC, Al species, and AC including glass phase by each SG range. Considering points 1, 4, and 6, CPA with particle size of 0.15-2.36 mm was selected for this experiment. Figure 4(a) shows the weight and UC distribution in each SG range after gravity sorting. The values ​​increased as the SG range (excluding 2.5SG and above) increased, with the range less than 1.8SG being the lowest at 16.8% and the range 2.2-2.5SG being the highest at 31.1%. It was also observed that the majority of UC was distributed in the low SG range, with the range less than 1.8SG being the highest at 54.7%, followed by 1.8-2.2SG, over 2.5SG, and 2.2-2.5SG at 39.6%, 4.1%, and 1.6%, respectively. Figure 4(b) shows the XRD peak changes of UC and AC for CPA separated by gravity separation at various SG ranges. This supports the UC distribution results in Figure 4(a) since only two XRD patterns show UC and AC peaks in the 1.8-2.2SG and below 1.8SG ranges. According to the results, Figure 4 shows that the most efficient SG value for separating UC and AC using gravity separation is 2.2SG.

[0053] 3-2: Flotation Flotation was performed under various solution conditions of pH 2, 7, and 12 to investigate the effect of pH on the adsorption kinetics of UC with air bubbles to confirm the effective separation of UC. Considering points 1, 2, and 5, CPA with particle size of 0.15 mm or less was selected in this experiment. Figure 5(a) shows the kinetic curves of UC adsorbed by air bubbles according to the flotation time. R indicates the UC adsorption (%) after the required flotation time and can be calculated as follows: [Mathematical formula 1] JPEG0007617109000003.jpg6170

[0054] Here, C0 and C represent the initial UC weight (mg) of untreated CPA and the weight (g) of the remaining UC (not separated) of CPA after flotation, respectively. All curves increased rapidly at the beginning and remained constant after 10 seconds. C at pH 7 R The highest concentration was 78.8% at pH 2, followed by 70.4% at pH 12 and 59.2% at pH 13. In the flotation mechanism, UC was adsorbed on the surface of bubbles generated at the bottom of the column and floated to the top of the solution. The adsorption of UC and bubbles can be expressed using a BET adsorption isotherm scaled by x (C) and y (U, the weight (g) of UC separated by the flotation line) axes. U is also expressed by the following equation: monolayer-max (Anderson, RB, 1946. J. Am. Chem. Soc. 68, 686-691). [Mathematical formula 2] JPEG0007617109000004.jpg5170

[0055] where k and U monolayer-max are the pre-exponential factor and the maximum weight (g) of UC that can be adsorbed by monolayer adsorption, respectively. In fact, as can be seen in Figure 5(b), the adsorption isotherm coincides with a multilayer curve. By rearranging Eq. (2), we obtain Eq. (3) as follows: [Mathematical formula 3] JPEG0007617109000005.jpg6170

[0056] In linear form, this equation has C as the x-axis. o / (C o ?C)U, C?C as Y axis, kU as gradient monolayer-max , with ?k as the y-intercept. Therefore, C o , C, and C calculated in U o The / (C?C)U value is ((C o As a result, at pH 7, the BET model is 2 The linear plot effectively described the adsorption isotherm with a k and U monolayer-max The values ​​of were confirmed to be -3.39 and 0.66(g), respectively. However, pH values ​​of 2 and 12 in Fig. 5(c) had little effect on the BET adsorption isotherm, which supports the results of the adsorption kinetics of UC shown in Fig. 5(a). From the results in Fig. 5, it was found that the collapse of the BET pattern at pH 2 and 12 conditions induced poor adsorption kinetics and reduced the separation efficiency of UC.

[0057] 3-3: Crushing According to point 5, grinding was performed with a particle size of 0.15 mm or less by grinding times of 5, 10, 20, and 40 minutes. Next, the change in particle size distribution of CPA according to grinding time and the effect of Fe oxide liberation were confirmed. Considering points 1, 2, 5, and 6, CPA with a particle size of 0.15 to 2.36 mm was selected for this experiment. Figure 6(a) shows the change in particle size distribution of CPA according to grinding time. After 20 minutes, most particles were crushed to <0.15 mm. Figure 6(b) shows images of CPA containing Fe oxide before grinding and Fe oxide liberated from CPA after grinding, respectively. Since Fe oxide is relatively strong compared to other substances in CPA, it was not broken when grinding under the conditions presented in '2-3: Grinding'. According to this result, Figure 6 clearly shows that grinding affects the effect of Fe oxide liberation.

[0058] 3-4: Magnetic sorting Magnetic separation was performed at four magnetic forces, 0.1, 0.5, 1, and 2T, to confirm the change in the recovery rate and purity of separated Fe oxides depending on the strength of each magnetic force. In order to confirm the separation effect of Fe oxides liberated by crushing in magnetic separation, three samples were selected in this experiment considering points 1, 2, 5, and 6. Two were CPA with particle sizes of 0.15-2.36 mm and less than 0.15 mm. The remaining one was CPA with particle sizes less than 0.15 mm, obtained by crushing particles to less than 0.15 mm with CPA with particle sizes of 0.15-2.36 mm. Figure 7 shows the recovery rate (Y Fe ) and purity (P Fe Here, we express the change in F o , F r , and W t Using the experimental data of Y Fe and P Fe was applied to estimate [Mathematical formula 4] JPEG0007617109000006.jpg5170 [Mathematical formula 5] JPEG0007617109000007.jpg5170

[0059] Here, F o and F s W represents the initial weight (g) of Fe oxide in the untreated sample and the weight (g) of Fe oxide in the material separated by magnetic separation, respectively. trepresents the total weight (g) of material separated by magnetic separation. As seen in Figure 7, as the magnetic strength increases, the recovery of Fe oxides separated by magnetic separation increases, whereas the purity decreases. For CPA with particle sizes between 0.15 and 2.36 mm, the recovery and purity values ​​at 0.1 T were 49% and 81%, respectively. When increased to 1 T, the recovery increased to 88%, whereas the purity decreased to 32%. For CPA with particle sizes below 0.15 mm, the recovery and purity at 0.1 T were 71% and 98%, respectively, which were higher than those with particle sizes between 0.15 and 2.36 mm. By increasing the magnetic strength to 1 T, the recovery increased to 95%, whereas the purity decreased to 56%. However, when increased from 1 T to 2 T, the values ​​did not change. In contrast, the values ​​for pulverized CPA are almost identical to those for CPA with particle sizes of 0.15 mm or less, indicating that pulverization enhances the separation effect of Fe oxides during magnetic separation.

[0060] Using the CPA characteristics, the overall flow chart (pretreatment process) shown in Figure 8 was derived, and experimental results were obtained. In this figure, first, in the first stage, CPA was screened and treated at 2.36 mm and 0.15 mm. At this time, wet screening can be applied to remove soluble chlorides. In the second and third stages, CPA with sizes of 0.15 to 2.38 mm and less than 0.15 mm were treated by gravity separation and flotation, respectively. In the fourth stage, a gravity separation process was performed by the first magnetic separation at 1 T (magnetic strength), and then materials containing Fe oxides were separated from the residue. Next, the materials containing Fe oxides were crushed using a crusher (stage 5). The residue from stage 2 and the material crushed in stage 5 were subjected to the second (0.1 T) and third (1 T) magnetic separation processes to separate Fe oxides. Thus, seven final by-products (Recovery 1 to 7) can be obtained from this pretreatment process. In addition, a laboratory-scale experiment was conducted using 200 kg of Boryeong CPA by the pretreatment method shown in Figure 8. Table 2 shows the separated amount and chemical composition of the final by-products (recoveries 1 to 7) for each step of the laboratory-scale experiment. The molecular weights of the coarse particles with UC purity of 28.4% in recovery 1 and the fine particles with UC purity of 62.1% in recovery 2 were 4.2 kg (2.1%) and 11.0 kg (5.5%), respectively. However, in recovery 3, the amount of the mixture of UC (purity 37.0%) and AC separated was 49.8 kg (24.8%). In the case of Fe oxide, the separated amounts of fine Fe oxide particles with purities of 94.8% and 42.2% in recovery 5 and 6 were 23.2 kg (11.6%) and 18.6 kg (9.3%), respectively. [Table 2]

[0061] The pretreatment method may be modified by various combinations of each separation step. Thus, the desired final by-product can be selectively obtained. Figure 9 shows various designs of pretreatment methods for the desired final by-product, and some examples are presented. Figure 9(a) shows that the mixture of UC and AC recovered after the gravity separation step can be separated with increased purity by additional grinding and flotation. However, the additional steps increase the energy cost. Also, the process shown in Figure 9(b) can increase the Fe oxide recovery rate compared to Figure 8. If the first magnetic separation step is omitted after the gravity separation step, the remaining second and third magnetic separation steps allow for a higher Fe oxide recovery rate from CPA. However, this increases the energy cost of grinding. To maximize the Fe oxide recovery rate, two pretreatment methods can be considered. Figure 9(c-1) is a method for recovering as much Fe oxide as possible while incurring the burden of high grinding energy costs, while Figure 9(c-2) is a method for recovering Fe oxide while reducing the reliance on grinding compared to Figure 9(c-1). Considering the separation of UC in Figure 9(c-1), a method like Figure 9(d) can be designed. In addition, the weak strength of CA is one of the main problems that hinder its use in construction sites (Mangi,SA et al.,2019.Resources 8(2),99;Luna,YLet al.,2014.Int.J.EnergyEnviron.Eng.5,387-397). Since UC and AC are substances that reduce the strength of CPA, as shown in Figure 9(e), the separation process of UC and AC can secure inorganic substances that can produce higher strength.

[0062] The recovered by-products can be used as recyclable materials in various industrial sectors with additional physical or chemical processes to meet the quality requirements of the final product. For example, UC can be a suitable carbon source for some applications. It can be used as a supplementary fuel in power plants and incineration plants or as a highly porous adsorbent (Evans, MJSet al., 1999. Carbon 37, 269-274; Lee, S. et al., 2014. Journal of Korean inst. of Resources Recycling 23, 40-47). It can also be a preferred alternative resource in the application of artificial graphite production, since natural graphite is considered a scarce commodity (Cabielles, M. et al., 2008. Energy Fuels 22, 1239-1243; Camean, I. et al., 2011. J. Power Sources 196, 4816-4820). In the case of AC with Al species and glassy phase, it can be a raw material for zeolite, an inorganic polymer used as a cation exchanger and adsorbent (Jin, X. et al., 2015. Procedia Eng. 121, 961-966; Lee, Y. et al., 2017. Chem. Eng. J. 317, 821-843; Penilla, RP et al., 2006. Fuel 85, 823-832). Zeolitic (synthetic) AC can also be used as a fixative, a hazardous element remover for polluted water, and a remediation element for polluted soil (Fernandez-Pereira, C. et al., 2002. J. Chem. Technol. Biotechnol. 77 (Issue 3); Sarkar, DK, 2015. Thermal Power Plant. Elsevier, pp. 139-158; Sarkar, M. et al., 2006. Waste Manag. 26, 559-570; Sitarz-Palczak, E. et al., 2012. J. Environ. Prot. (Irvine, Calif) 3, 1373-1383).

[0063] To confirm the current status of CPPs and CPAs in Korea, we investigated the number and location of CPPs, combustion method, generating capacity, type of coal used, and AP. Table 3 shows the characteristics of 11 coal-fired power plants in Korea. Ten of the 11 CPPs are currently in operation, and the remaining one is the Sachon CPP, which was suspended in 2017. [Table 3]

[0064] All CPPs are located in coastal areas and can use seawater to cool the high temperature of CA generated after combustion. Figure 1 is a map showing where each CPP is located around the coast. The AP-related drawings located around Boryeong Thermal Power Plant on the map are excerpted from Lee's paper (Lee, SJ et al., 2007, Geosystem Eng. 10, 47-52). Most of the combustion methods of each CPP are operated by pulverized coal combustion (PCC) method. Recently, Donghae Thermal Power Plant (400 MW) and Yeosu Thermal Power Plant (340 MW) have been built and are operated by circulating fluidized bed combustion (CFBC) method. CA generated by PCC type is characterized by pozzolanic reactivity and contains glassy aluminosilicate formed at high combustion temperatures (1300℃~1700℃) (Cheriaf, M. et al., 1999. Cem. Concr. Res. 29(9), 1387-1391). This is consistent with the results of the CPA characteristics (Al-based AC and glass phase) of the PCC-type Boryeong thermal power plant mentioned above. However, the CA of the CFBC is rich in glass lime (Free CaO) and anhydrous gypsum due to the limestone added during the desulfurization process, and has its own hardening characteristics (Sheng, G. et al., 2012. Fuel 98, 61-66). In terms of power generation capacity, the recently expanded Danjin (6,040MW), Yeongheung (5,080MW), and Daean (6,100MW) produce high thermal energy, followed by Boryeong (4,000MW), Hadong (4,000MW), and Samcheongpo (3,240MW). The type of coal used as the main fuel at each CPP is mostly bituminous coal, and only the small-scale Yeongdong and Donghae use anthracite. Anthracite has good calorific value due to its high fixed carbon content (85-90%) despite its low volatility (3-7%). However, its slow burning speed makes it unsuitable as a fuel for power generation. In contrast, bituminous coal contains a large amount of volatile matter and emits flames. Each CPP operates an AP for the disposal of CA, and only small CPPs in Honam, Donghae, and Yeosu areas outsource the disposal to nearby CPPs that operate their own APs. Based on AP capacity and landfill volume, Boryeong has 23,160,000 m 3and 32.9 MT, which is the largest CPP, followed by Danjin (17,560,000 m 3 and 24.9MT), Samcheonpo (13,380,000m 3 and 14.6MT).

[0065] The proposed pretreatment method is based only on the CPA in the Boryeong area. Therefore, the separation method and the actual separated materials may differ depending on the CPA buried in each AP (7 APs in Korea in total). However, according to the above-mentioned survey, it was found that the overall characteristics of the CPA are affected by the combustion method and the type of coal used. Since most CPPs are operated by the PCC method and mainly use bituminous coal as the main fuel, most CPAs (more than 92% of the total CPAs in Korea) are expected to have glass aluminosilicate and pozzolanic reactivity as shown in Table 3. In addition, the UC content is relatively low. Therefore, it can be assumed that the CPA buried in the APs near the Boryeong CPP represents all CPAs in Korea. The CPAs in each AP will probably differ only in the content percentage of each item in the chemical composition. Therefore, it is predicted that there will be no problem if this pretreatment method is applied to all CPAs in Korea. In fact, in the proposed pretreatment method, a material flow analysis of CPA can be predicted using the total amount of CPA landfilled in all APs in Korea (~1,517.5 MT, see Table 3). After pretreatment, the by-products containing Fe oxides were 317.1 MT, followed by carbon (115.3 MT), amorphous materials (376.4 MT), and inorganic materials mainly composed of Si and Al (708.7 MT).

[0066] A large amount of CA is generated from CPPs. Despite many governmental supports, policy improvements, and technological efforts to increase the recycling rate of CA, each CCP still disposes of CA by landfilling it in nearby APs. Currently, most of the APs are fully buried, and local residents are increasingly concerned about the possibility of environmental pollution around the APs. Therefore, in this study, in order to properly utilize CPA (representing CA buried in APs), the characteristics of CPA were investigated based on particle size and weight distribution, chemical composition, UC content, particle image, and mineralogical analysis. Based on these results, a pretreatment method for the utilization of CPA was designed based on screening (standard sieves with 2.38 mm and 0.15 mm diameter grids), gravity separation (2.2SG), flotation (pH 7), crushing (less than 0.15 mm), and magnetic separation (0.1 and 1T). Seven final by-product groups with different compositions were obtained depending on the separation method and the size of the fine particles: (1) coarse particles containing UC, 2.1 wt% separation amount; (2) fine particles containing UC, 5.5 wt%; (3) mixture of UC and AC, 24.8 wt%; (4) coarse particles containing inorganic substances mainly containing Si and Al, 19.5 wt%; (5) fine particles containing high purity Fe oxide, 11.6 wt%; (6) fine particles containing low purity Fe oxide, 9.3 wt%; (7) fine particles containing inorganic substances mainly containing Si and Al, 27.2 wt%. Six additional pretreatment methods were proposed using various combinations of each separation step, taking into account the purpose, energy cost, and recovery efficiency of the desired final material.

[0067] It was confirmed that the pretreatment method proposed in the present invention can be applied to CPA in Korea. However, since the method according to the present invention is merely an intermediate treatment to increase the recycling efficiency in the final recycling process, the potential direction of research on each detailed matter may be further discussed. In addition, a pretreatment method similar to the present invention must be developed by logically examining the characteristics of various CPAs due to the differences in the characteristics of CPAs in each country. Nevertheless, the pulverized coal combustion (PCC) method, which is the main method for burning coal, has led to the construction of large-scale power plants and is therefore the most widely used method in CPPs worldwide, including Korea (Sarkar, M. et al., 2005. J. Chem. Technol. Biotechnol. 80 (Issue 12)). According to the global supply structure of coal categories based on weight by Xia et al., bituminous coal accounts for 73.85% of the world's coal supply, while anthracite accounts for 1.38% (Xia, X. et al., 2017. J. Clean. Prod. 143, 125-144). Therefore, CPPs around the world use bituminous coal as their main fuel. Considering this fact, when comparing the CPAs in most other countries with the CPAs in this study, it can be predicted that only the content ratios of items, etc. in the chemical composition may differ. Therefore, there will be no problem in applying the pretreatment method according to the present invention to CPAs in other countries. In addition, if the results obtained from the present invention are directly applied to similar industries in other countries, they can serve as a basis for designing new CA pretreatment plants to be landfilled in AP or modifying existing designs.

[0068] The aim is to identify the feasibility of adopting a recycling strategy, moving away from the existing simple landfill treatment method. Globally, it is considered that the proposed method could bring significant benefits, especially in relation to the savings in environmental protection costs, including landfill treatment, maintenance and periodic environmental monitoring costs around the AP environment. There may also be savings in the economic penalties around the landfill ponds and indirect environmental costs associated with activities such as restoration of contaminated areas. A detailed cost analysis of implementing such a pretreatment method on a wider scale would be well within the scope of further studies. [Industrial Applicability]

[0069] The pretreatment method according to the present invention can improve the utilization of landfill coal ash generated at coal-fired power plants and buried in landfill ponds, and can classify the coal ash into unburned carbon, amorphous compounds containing Al species (Al2O3·xH20) and a glass phase, inorganic substances containing Si and Al, and iron substances. It can also be directly applied to similar industries in other countries to provide a basis for the design of new or modification of existing pretreatment plants for coal ash that is to be disposed in landfill ponds.

[0070] As described above, certain parts of the present invention have been described in detail. It will be apparent to those skilled in the art that such specific techniques are merely preferred embodiments and do not limit the scope of the present invention. Therefore, the substantial scope of the present invention is defined by the claims and their equivalents.

Claims

1. A method for pretreatment of coal landfill ash (CPA) comprising the steps of: (a) screening landfill coal ash, which is composed of a mixture of fly ash and bottom ash, using a sieve to classify the landfill coal ash into coarse particles, medium particles and fine particles; (b) subjecting the particles obtained in step (a) to flotation; (c) subjecting the intermediate particles obtained in step (a) to float-sink separation; and (d) mixing the residue obtained in step (b) with the residue obtained in step (c), and then subjecting the mixture to magnetic separation to obtain fine materials containing Fe oxide and fine materials containing Si and Al, In step (a), the landfill coal ash is classified into coarse particles having a diameter exceeding 2.36 mm, medium particles having a diameter of 0.15 to 2.36 mm, and fine particles having a diameter less than 0.15 mm using standard sieves having meshes with diameters of 0.15 mm and 2.36 mm; Step (b) is carried out at pH 7; In the step (c), gravity separation is performed using a solution having a specific gravity of 2.2; and In step (d), high-purity Fe oxide-containing fine materials are separated from the mixture of the residue obtained in step (c) and the residue obtained in step (b) using a 0.1 T wet magnetic separator, and then low-purity Fe oxide-containing fine materials are separated using a 1.0 T wet magnetic separator. A method for pretreatment of landfill coal ash (CPA).

2. 2. The method for pretreating landfill coal ash (CPA) according to claim 1, further comprising the step of: subjecting the obtained residue to wet magnetic separation at a magnetic strength of 1.0 T after performing step (c), and grinding the separated Fe oxide-containing material to a size of less than 0.15 mm.

3. The method for pre-treating landfill coal ash (CPA) according to claim 1, characterized in that the landfill coal ash (CPA) is generated from a coal-fired power plant (CPP) and buried in an amphibious pond (AP).

4. A method for obtaining a by-product having increased purity of unburned carbon (UC) and amorphous components (ACs) from landfill coal ash (CPA), comprising the steps of: (a1) screening and recovering landfill coal ash comprising a mixture of fly ash and bottom ash; (a2) screening, flotation and recovering landfill coal ash; (a3) screening, gravity separating, pulverizing, flotation and recovering the landfill coal ash; (a4) screening, gravity separation, magnetic separation and recovery of the landfill coal ash; (a5) screening, gravity separation, primary magnetic separation and pulverization of the landfill coal ash to obtain a by-product, mixing the by-product with the residue obtained in step (a2), and then subjecting the by-product to secondary magnetic separation and recovery; and (a6) magnetically separating and recovering the residue obtained in (a5), In the screening step, the landfill coal ash is classified into coarse particles having a diameter exceeding 2.36 mm, medium particles having a diameter between 0.15 and 2.36 mm, and fine particles having a diameter less than 0.15 mm using a standard sieve having a mesh with a diameter of 0.15 mm and 2.36 mm; The flotation step is carried out at pH 7; The gravity separation step is carried out using a solution having a specific gravity of 2.2; and In the magnetic separation step, a high-purity Fe oxide-containing fine material is separated from the mixture of the residue obtained in the floatation step and the residue obtained in the gravity separation step using a 0.1 T wet magnetic separator, and then a low-purity Fe oxide-containing fine material is separated using a 1.0 T wet magnetic separator. The method.

5. A method for obtaining a by-product having increased Fe oxide recovery from coal landfill ash (CPA), comprising the steps of: (b1) screening and recovering landfill coal ash comprising a mixture of fly ash and bottom ash; (b2) screening, flotation and recovering the landfill coal ash; (b3) screening, gravity separating and recovering the landfill coal ash; (b4) screening, gravity separating and pulverizing the landfill coal ash to obtain a by-product, mixing the by-product with the residue obtained in step (b2), and then magnetically separating and recovering the by-product; and (b5) magnetically separating and recovering the residue obtained in (b4), In the screening step, the landfill coal ash is classified into coarse particles having a diameter exceeding 2.36 mm, medium particles having a diameter between 0.15 and 2.36 mm, and fine particles having a diameter less than 0.15 mm using a standard sieve having a mesh with a diameter of 0.15 mm and 2.36 mm; The flotation step is carried out at pH 7; The gravity separation step is carried out using a solution having a specific gravity of 2.2; The grinding step is carried out to have a size of less than 0.15 mm; and In the magnetic separation step, a high-purity Fe oxide-containing fine material is separated from the mixture of the residue obtained in the floatation step and the residue obtained in the gravity separation step using a 0.1 T wet magnetic separator, and then a low-purity Fe oxide-containing fine material is separated using a 1.0 T wet magnetic separator. The method.

6. A method for obtaining only Fe oxides from coal landfill ash (CPA) comprising the following steps: (c1) crushing, magnetically separating and recovering landfill coal ash consisting of a mixture of fly ash and bottom ash; or (c2) crushing, primary magnetic separation, secondary magnetic separation and recovery of the landfill coal ash; The grinding step is carried out to have a size of less than 0.15 mm, In the magnetic separation step, a high-purity Fe oxide-containing fine material is separated from the residue mixture obtained in the pulverization step using a 0.1T wet magnetic separator, and then a low-purity Fe oxide-containing fine material is separated using a 1.0T wet magnetic separator. The method.

7. The method for obtaining only Fe oxides from landfill coal ash (CPA) according to claim 6, characterized in that magnetic separation is further performed before the pulverization of (c1) and (c2) in order to reduce the energy cost of the pulverization step.

8. A method for obtaining only unburned carbon and Fe oxides from landfill coal ash (CPA), comprising the steps of: (d1) crushing, flotation and recovering landfill coal ash consisting of a mixture of fly ash and bottom ash; (d2) crushing, flotation, magnetic separation and recovery of the landfill coal ash; or (d3) crushing, flotation, primary magnetic separation, secondary magnetic separation and recovery of the landfill coal ash; The flotation step is carried out at pH 7; The grinding step is carried out to have a size of less than 0.15 mm; and In the magnetic separation step, a high-purity Fe oxide-containing fine material is separated from the residue mixture obtained in the pulverization step using a 0.1T wet magnetic separator, and then a low-purity Fe oxide-containing fine material is separated using a 1.0T wet magnetic separator. The method.

9. A method for obtaining an increased strength by-product from landfill coal ash (CPA) comprising the steps of: (e1) screening and recovering landfill coal ash comprising a mixture of fly ash and bottom ash; (e2) screening, flotation and recovering the landfill coal ash; or (e3) screening, gravity separating and recovering the landfill coal ash; In the screening step, the landfill coal ash is classified into coarse particles having a diameter exceeding 2.36 mm, medium particles having a diameter between 0.15 and 2.36 mm, and fine particles having a diameter less than 0.15 mm using a standard sieve having a mesh with a diameter of 0.15 mm and 2.36 mm; the flotation step is carried out at pH 7; and The gravity separation step is carried out using a solution having a specific gravity of 2.

2. The method.

Citation Information

Patent Citations

  • Method for recycling coal ashes in power plant

    CN102530966A

  • Process for making a ceramic particulate mixture

    EP3640227A1

  • Adjustment method of color tone of fly ash and fly ash whose color tone is adjusted

    JP2021053561A

  • A fly ash purify and product collection method

    KR101024540B1

  • Recovering method of high purity ash using bottom ash and fly ash

    KR101243094B1